Pengaruh Safety Culture terhadap Safety Behavior pada Unit PKP- PK di Bandar Udara Internasional Adi Soemarmo Solo - Sewet, Fahrurrozi; Jumlad, Walid (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Working following work safety procedures is one of the safety behaviors that must be carried out at the PKP-PK unit at Adi Soemarmo Solo International Airport, to realize the company's goals, it is necessary to have a safety culture that is rooted in the organization or each - each officer. So this study aims to: (1) Determine the influence of safety culture on safety behavior at the PKP-PK unit at Adi Soemarmo Airport, Solo and (2) Find out how much influence safety culture has on safety behavior at the PKP-PK unit at Adi Airport Soemarmo Solo. The method used in this study is a quantitative method with a total of 33 personnel in the PKP-PK unit at Adi Soemarmo Airport, Solo. The data collection technique used a questionnaire, the data obtained was then analyzed using a simple linear regression test, the F test, t test, and the coefficient of determination test (R2). The results of this study are (1) safety culture has a significant effect both partially and simultaneously on safety behavior at the PKP-PK unit at Adi Soemarmo Airport, Solo and (2) the influence of safety culture on safety behavior at the PKP-PK unit at the Airport Adi Soemarmo Solo by 81,6%. Keywords : Safety Culture, Safety Behavior, PKP-PK.